2011
DOI: 10.1007/s10461-011-9948-4
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Correlates of Internalized Homophobia Among Men Who Have Sex with Men in Pretoria, South Africa

Abstract: This study examines levels and correlates of internalized homophobia among men who have sex with men (MSM) in Pretoria, South Africa. Using respondent-driven sampling, we recruited 324 MSM from February to August 2009. Results were adjusted using RDSAT analysis to yield population-based estimates. High levels of internalized homophobia exist among South African MSM: 10-15% reported "often/very often" and over 20% reported "sometimes" having feelings of internalized homophobia. A greater level of internalized h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 31 publications
6
57
1
Order By: Relevance
“…In fact, there was a higher likelihood of men with greater IH to have been diagnosed with an STI in the past year, which may be related to not only knowledge, but the previously discussed results about the ability to refuse unwanted sex and feelings of loneliness. Lastly, we mention that contrary to other studies Vu et al, 2012), we found that IH was higher in MSM with higher education. There is no obvious explanation for this finding but it may be an artefact, it may be because higher educated men believe they have more to lose by being "outed," and it may be related to awareness of cultural heterosexism.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In fact, there was a higher likelihood of men with greater IH to have been diagnosed with an STI in the past year, which may be related to not only knowledge, but the previously discussed results about the ability to refuse unwanted sex and feelings of loneliness. Lastly, we mention that contrary to other studies Vu et al, 2012), we found that IH was higher in MSM with higher education. There is no obvious explanation for this finding but it may be an artefact, it may be because higher educated men believe they have more to lose by being "outed," and it may be related to awareness of cultural heterosexism.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with our hypothesis and prior work (Franssens, 2010;Kuyper & Fokkema, 2011;Vu et al, 2012), IH was higher in nongay identified MSM compared with those who identified as gay (or homosexual). It is possible that self-identification as gay indicates a higher degree of self-acceptance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations